2016
DOI: 10.1007/s10798-016-9387-7
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the relation between students’ implicit beliefs about their abilities and their educational STEM choices

Abstract: Despite the large body of research on students' educational and career choices in the field of technology, design, and science, we still lack a clear understanding of how to stimulate more students to opt for a study path or career within the STEM fields (Science, Technology, Engineering, Mathematics). In this article, we outline a new theoretical framework to describe how students' implicit belief about the malleability of their intelligence can be an important precursor of their STEM educational and career c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
31
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 46 publications
(36 citation statements)
references
References 96 publications
(194 reference statements)
2
31
1
Order By: Relevance
“…This study provides the first empirical support for the idea that implicit beliefs about STEM ability predict students' intention to opt for a STEM bachelor's degree. Our findings furthermore support the hypothesized assumption that self‐efficacy beliefs mediate the relation between implicit beliefs and STEM intention (van Aalderen‐Smeets & Walma van der Molen, ). Consistent with previous research, we found that the more students endorsed incremental beliefs about their STEM ability, the more positive STEM self‐efficacy beliefs they reported (Robins & Pals, ).…”
Section: Discussionsupporting
confidence: 87%
See 4 more Smart Citations
“…This study provides the first empirical support for the idea that implicit beliefs about STEM ability predict students' intention to opt for a STEM bachelor's degree. Our findings furthermore support the hypothesized assumption that self‐efficacy beliefs mediate the relation between implicit beliefs and STEM intention (van Aalderen‐Smeets & Walma van der Molen, ). Consistent with previous research, we found that the more students endorsed incremental beliefs about their STEM ability, the more positive STEM self‐efficacy beliefs they reported (Robins & Pals, ).…”
Section: Discussionsupporting
confidence: 87%
“…The either direct or indirect contribution of implicit ability beliefs to the intention to opt for a STEM‐oriented education or career (called STEM intention) has been suggested by other studies as well (Blackwell, Trzesniewski, & Dweck, ; Burkley, Parker, Stermer, & Burkley, ; Dweck, , ; Murphy & Thomas, ; Nix, Perez‐Felkner, & Thomas, ; van Aalderen‐Smeets & Walma van der Molen, ; Wang & Degol, ). In addition, there is a range of research that has indicated the importance of students' achievement goal orientations, both in general education and in mathematics education (e.g., Fadlelmula, ; Midgley, ).…”
mentioning
confidence: 78%
See 3 more Smart Citations